Optimalisasi Waktu dan Biaya Proyek Gelora Ahmad Yani Mojokerto Menggunakan Metode Time Cost Trade Off - Susila Bayu Aji; A'izzatul Khiyana; Totok Yulianto; Titin Sundari (Jurnal Talenta Sipil, 2026)
The Gelora Ahmad Yani Infrastructure Project in Mojokerto experienced delays from week 5 to week 7, which could extend the project duration and increase construction costs. These delays required a measurable time and cost control evaluation to ensure more efficient project completion. This study aimed to determine the most optimal acceleration alternative for the project using the Time Cost Trade Off (TCTO) method. The research data consisted of the Budget Plan, project schedule, progress reports, working-hour data, and heavy equipment data. The analysis was conducted on critical path activities by comparing acceleration scenarios involving 1, 2, 3, and 4 hours of overtime work and the addition of a mini roller. The results show that the normal project condition had a duration of 90 days with a total cost of IDR 870,542,000.00. The most optimal alternative was the addition of heavy equipment, which produced a final duration of 25 days, representing an acceleration of 65 days or 72.22%. The total project cost decreased to IDR 843,848,152.79, with a saving of IDR 26,693,847.21 or 3.07% compared with the normal cost. Therefore, adding a mini roller is recommended as a more effective acceleration strategy, particularly for critical paving activities.